Competence and work facilities influence employee performance through the mediating role of job satisfaction. - Ongkowidjojo, Anita; Iramani, Rr; Yulianti, Emma (Manajemen dan Bisnis, 2025)
This study aims to examine the effect of competence, work facilities, and job satisfaction on employee performance at the Public Health Centre in the North Surabaya area. This study uses a quantitative approach with data collection through questionnaires. The research sample consisted of 150 Public Health Centre employees in the North Surabaya area who had worked for at least 2 years who were selected by purposive sampling. Data were analyzed using Structural Equation Modelling (SEM) techniques with Partial Least Square (PLS). The results showed that competence, work facilities, and job satisfaction have a significant positive effect on employee performance. Job satisfaction also indirectly mediates the effect of competence and work facilities on employee performance. This study suggests that the Public Health Centre can continue to improve the competence of its employees through training, provide adequate work facilities, and pay attention to job satisfaction factors to improve employee performance. These findings provide practical implications that by increasing the competence of employees and adequate work facilities can lead to job satisfaction of employees so that their performance will also increase.